2010
DOI: 10.1017/s002966511000073x
|View full text |Cite
|
Sign up to set email alerts
|

Cellular immune response in intestinal villi of rats after consumption of onion (Allium cepa L.) or Quercetin

Abstract: Mucosal epithelia are primary sites for antigen entry. The microenvironment in these mucosal barriers has a marked influence on the immune response that ultimately ensues (1) . The bioactive compounds present in foods would have an impact on the immunocompetence, especially in the intestinal villi (IV). In this way, the attention is focused on the possibility of modulating the immune response for enhancing health and quality life.Allergy problems due to dietary factors were increased during the last few years … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 2 publications
0
2
0
Order By: Relevance
“…Research conducted so far on the role of garlic and onions in the prevention and alleviation of the course of diseases and ailments of the digestive tract is apparently insufficient, inconsistent, incomplete, and often contradictory. Moreover, they relate to various forms of garlic and onion use (fresh vegetables, fresh extract, freeze-dried forms, oil, and isolated compounds), supplementation time and dose, and finally various animal research models (e.g., rats [67][68][69][70][71][72][73], mice [74], pigs [75], broilers, and chickens [76][77][78][79]) with induced injuries of the gastrointestinal tract [67,69,71,73,74] or infected with pathogenic microorganisms [74]. In the available literature, no information was found on the effect of the addition of raw Alliaceae plants, administered in an atherogenic diet, on morphological changes in the intestine.…”
Section: Introductionmentioning
confidence: 99%
“…Research conducted so far on the role of garlic and onions in the prevention and alleviation of the course of diseases and ailments of the digestive tract is apparently insufficient, inconsistent, incomplete, and often contradictory. Moreover, they relate to various forms of garlic and onion use (fresh vegetables, fresh extract, freeze-dried forms, oil, and isolated compounds), supplementation time and dose, and finally various animal research models (e.g., rats [67][68][69][70][71][72][73], mice [74], pigs [75], broilers, and chickens [76][77][78][79]) with induced injuries of the gastrointestinal tract [67,69,71,73,74] or infected with pathogenic microorganisms [74]. In the available literature, no information was found on the effect of the addition of raw Alliaceae plants, administered in an atherogenic diet, on morphological changes in the intestine.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, in a previous report, our group demonstrated that Quercetin (CAS No. 117-39-5), a naturally occurring dietary polyphenol, would have a potential immune-regulatory effect in allergic processes ( 3 ) .…”
mentioning
confidence: 99%